Response to 'Presentation and pathophysiology of neuro-COVID' - Daniele Orsucci; Marco Vista (BioExcel Publishing Ltd, 2021)
Letter to the Editor in response to Finsterer J, Scorza FA, Scorza CA. Presentation and pathophysiology of neuro-COVID. Drugs Context. 2021;10:2021-6-5. https://doi.org/10.7573/dic.2021-6-5